Constructivist Learning Models Based on LKPD to Enhance Higher Order Thinking Skills: A Systematic Literature Review - Mutiasari, Aprilia; Adha, Muhammad Mona; Nugraheni, Irma Lusi; Wahyudi, Apri (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
The development of the 21st century education paradigm demands a learning approach that is able to develop learners’ high-level thinking skills (HOTS), such as analysis, evaluation, and creation. One effective approach is the constructivism model, which focuses on the active role of learners in building knowledge through direct experience, social interaction, and reflection. This study aims to examine the application of constructivism learning model based on LKPD (Learner Worksheet) to improve HOTS of high school students. The method used is systematic literature review (SLR) which analyzes various previous studies related to the application of constructivism in developing HOTS. The results showed that the use of LKPDs designed according to the principles of constructivism and supported by project-based learning strategies, inquiry, and problem solving effectively improved students’ critical, analytical, and creative thinking skills. In addition, the application of this model is also able to improve the collaboration, creativity, and character of learners, making it relevant to prepare a generation of adaptive and innovative learners to face global challenges. This finding confirms the importance of integrating constructivism and HOTS approaches in the modern education curriculum